A online learning and the effectiveness of islamic ethic e-learning technology - Teni Teni; Agus Yudianto (Institute of Accounting Research and Novation (IARN), 2023)
A What is the relationship between online learning and e-learning technology that is managed in learning in the internet world. What is the value of the concept of online learning and e-learning technology. And how the paper articulates this concept acts to position mobile technology devices as 'technology for online learning and e-learning. Actor-network theory (ANT) categories of information about discursive practices used to position technology in relation to learning.